Knockdown of long noncoding RNA-taurine-upregulated gene 1 inhibits tumor angiogenesis in ovarian cancer by regulating leucine-rich α-2-glycoprotein-1. Issue 6 (July 2019) - Fan, Mingjun; Li, Chunyan; He, Pengjuan; Fu, Yibing; Li, Mingjiang; Zhao, Xingbo
Abstract : To investigate the role of long noncoding RNA taurine-upregulated gene 1 ( TUG1 ) on ovarian cancer-induced angiogenesis and to explore possible signaling pathways. Ovarian cancer cell line SKOV3 or CAOV3 was transfected with short hairpin- TUG1 to suppress TUG1 expression. Supernatant from cultured cancer cells was used as a condition medium to incubate endothelial cell line human umbilical vein endothelial cells, whose proliferation rate was quantified by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Migration and invasion of endothelial cells were examined by wound healing and Transwell assays, followed by in-vitro angiogenesis assay. One of the secretory factors mediating angiogenesis, leucine-rich α-2-glycoprotein-1 (LRG1), was measured in ovarian cancer cells. Signaling pathway mediating angiogenesis was further detected by western blotting. TUG1 was down-regulated in ovarian cancer cells by short hairpin RNA. Conditional medium originating from TUG1 -knockdown cancer cells led to suppressed proliferation, migration, or invasion of endothelial cell line human umbilical vein endothelial cells. LRG1 expression and secretion was suppressed in ovarian cancer cells after TUG1 knockdown. Moreover, recombinant LRG1 rescued TUG1 knockdown-induced angiogenesis inhibition, and LRG1 probably mediated angiogenesis by tumor growth factor-β signaling pathway in endothelial cells. Long noncoding RNA- TUG1 mediates angiogenesis of endothelial cells by regulating LRG1 secretion from ovarian cancer cells partially through tumor growth factor-β pathway. Our results indicate the potency of TUG1 as a biomarker and therapeutic target for tumor-induced angiogenesis. Abstract : Supplemental Digital Content is available in the text.